PENGARUH METODE PENERAPAN PEMBELAJARAN DAN KINERJA GURU TERHADAP PRESTASI BELAJAR SISWA DI SD NEGERI DI KECAMATAN JATIBARANG KABUPATEN INDRAMAYU - Watini Watini; Dinny Kristianty W (Pascasarjana Unviersitas Majalengka, 2022)
This research is motivated by the low results of the teacher competency test which is a reflection of the low teaching performance of teachers in Indonesia, which of course is related to the low HDI and the Education Development Index or the Indonesian Education Development Index in UNDP and Unesco research monitoring. The low performance of teachers in Indonesia is caused by many factor. This study uses a descriptive correlational method. This method describes the relationship between research variables. This study uses a descriptive correlational method. This method describes the relationship between research variables. The results showed that the learning method applied at SD Negeri Lohbener Lor in Jatibarang District, Indramayu Regency was based on the results of the research and the discussion was perceived as good. The teacher's performance at SD Negeri Lohbener Lor in Jatibarang District, Indramayu Regency is based on the results of research and discussions that are perceived as good. Student achievement at SD Negeri Lohbener Lor in Jatibarang District, Indramayu Regency is based on the results of research and discussion that are perceived as good. There is an influence of learning methods on learning achievement of SD Negeri Lohbener Lor in Jatibarang District, Indramayu Regency. There is an influence of teacher performance on learning achievement at SD Negeri Lohbener Lor in Jatibarang District, Indramayu Regency. There is an influence of learning achievement and teacher performance on learning achievement at SD Negeri Lohbener Lor in Jatibarang District, Indramayu Regency